Monday

July 28, 2014

July 28, 2014

Posted by **Sarah** on Wednesday, August 15, 2007 at 4:51pm.

I would factor out 2x to give

2(x+3)=0

2x^2 = -6x;

2x = -6;

x = -3.

hopefully thts the answer!

**Related Questions**

math - how would you solve for y in this problem: x=(y^2+3y)^(1/3) would it ...

math - solve the equation x^3-5x^2-4x+20=0 I need a hint on how to solve this ...

math - The "x intercept" is where y = 0, which is where the curve crosses the x ...

math,algebra - can someone help me out factor out this 0=16t^2-122t+180 i have ...

algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...

Math - -x^3 + 1.85x^2 - x +0.15 = 0 how can you solve for x? An exact solution ...

advanced math - Hi, I am trying to solve graphing quadratic equations. One of ...

algebra - It is not solvable by that method, shanaid. You have to get all the ...

maths - for this equation x^2 - x = 0 would x = 1 i think this is the answer but...

Math - How can I find the point of intersection of the graphs x^2=y=4 and 2x-y=1...